On the General Interpolation Formulas for Discrete Functional Spaces (Ⅰ) (Journal of Computational Mathematics, 1993)
The general interpolation formulas for discrete functional spaces of discrete functions with one index are presented in the note. These are the relationship among the discrete norms in the forms of the summation of powers, the maximum modulo, the Hölder and Lipschitz coefficients for the discrete functions.